A Case of a Ruptured Liver Abscess Presenting as Free Air After a Pylorus-preserving Pancreatoduodenectomy - Ozaki, Masahiko; Oshima, Ikuya; Kinoshita, Hirohisa; Shinoto, Koichi; Shoko, Tomohisa (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2003)
We report a gas-producing pyogenic abscess in the liver and review similar cases reported in Japanese medical literature. A 60-year-old male with a past history of diabetes mellitus was admitted to hospital complaining of a high fever and general malaise. He had undergone a pylorus-preserving pancreatoduodenectomy for the treatment of pancreatic head cancer. Ultrasonography and CT examinations showed a gas-producing pyogenic abscess in the right lobe of the liver. Percutaneous transhepatic drainage of the abscess was performed under ultrasonographic guidance. Klebsiella pneumoniae was detected in a culture of the abscess' contents. Both intrahepatic and subphrenic abscesses were successfuly drained, and the abscesses gradually decreased in size. Four weeks after drainage, the patient died from bleeding in the gastrointestinal tract, probably as a result of the local recurrence of pancreatic head cancer.